PEMBELAJARAN BAHASA INGGRIS SECARA DARING DALAM PERSPEKTIF FILSAFAT PERENIALISME - Md. Yudyantara Risadi; Ni Luh Putu Uttari Premananda (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
This study aimed at examining how teaching English subject matter was reviewed from perennialism theoritically. It is undeniably that education could not be separated from any philosophies that became the basic of learning and teaching situation. One of the philosophies becoming the basic of education is perennialism. Perennialism states that education tends to be religious and religion-rule oriented, focuses on old tradition and culture, and bases on the unity to find equations. This study used library research to combine all the theories from trusted sources and the data analysis used was content analysis. The findings were education, especially English subject matter in perennialism view could be done properly if there is a disipline mental, thought principality and independence by giving students chance to speak , learning to reason by helping the students to find any reason to study, studying for life preparation by doing poilteness, and learning through teaching in which the teacher becomes facilitator of the online teaching and learning process. The point of perennialism in English subject matter is being able to make the students more polite, the learning process continues systematically, and always keep in mind the culture and custom of Indonesia.